2010
DOI: 10.1007/s10544-010-9491-5
|View full text |Cite
|
Sign up to set email alerts
|

Implantable drug delivery device using frequency-controlled wireless hydrogel microvalves

Abstract: This paper reports a micromachined drug delivery device that is wirelessly operated using radiofrequency magnetic fields for implant applications. The controlled release from the drug reservoir of the device is achieved with the microvalves of poly(N-isopropylacrylamide) thermoresponsive hydrogel that are actuated with a wireless resonant heater, which is activated only when the field frequency is tuned to the resonant frequency of the heater circuit. The device is constructed by bonding a 1-mm-thick polyimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…In order to maximize the drug reservoir volume of the device, the actuation mechanism has to be minimalistic yet effective. Examples of such minimalistic methods include electrochemical method [30], electrothermal method [35] (Figure 2), and passive method [13]. In general, delivery methods for BioMEMS devices fall into three main categories: (i) actuation-less methods, (ii) single chamber actuation methods and (iii) multi-chamber actuation methods.…”
Section: Effective Delivery Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to maximize the drug reservoir volume of the device, the actuation mechanism has to be minimalistic yet effective. Examples of such minimalistic methods include electrochemical method [30], electrothermal method [35] (Figure 2), and passive method [13]. In general, delivery methods for BioMEMS devices fall into three main categories: (i) actuation-less methods, (ii) single chamber actuation methods and (iii) multi-chamber actuation methods.…”
Section: Effective Delivery Methodsmentioning
confidence: 99%
“…A popular microvalve used for this BioMEMS design is a thermosensitive material known as hydrogel. Rahimi et al [35] have demonstrated that by using radio frequency telemetry, heat can be generated within a coil in contact with the hydrogel microvalves, causing the hydrogel to contract, thus opening the valves for delivering drugs via passive diffusion ( Figure 2). The overall size dimension of the device is approximately 5 mm × 5 mm × 4 mm and has a drug reservoir size of about 78 uL.…”
Section: Effective Delivery Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include, but are not limited to, the use of ultrasound [8], light waves [9], magnetic fields [10] and radio waves below 100 MHz [11]. Complex systems have also been integrated into a drug delivery module consisting of a receiving inductor, control circuitry chip and a drug delivery chip [12].…”
Section: Introductionmentioning
confidence: 99%